CNN-watershed: A machine learning-based tool for delineation and measurement of ice wedge polygons in high-resolution digital elevation models - Abolt, Charles J; Young, Michael H; Atchley, Adam L; Wilson, Cathy J (Zenodo, 2019)
This repository contains data and code used in the paper "Rapid machine-learning-based extraction and measurement of ice wedge polygons in high-resolution digital elevation models" by Abolt et al . in The Cryosphere (2019). See the included README file for instructions on usage.